1980
DOI: 10.1136/jcp.33.10.917
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes in inflammatory bowel disease: absolute monocyte counts.

Abstract: Using a cytochemical staining technique, peripheral blood monocytes have been precisely identified and enumerated in patients with inflammatory bowel disease and compared with healthy and disease control subjects. For ulcerative colitis there was a significant monocytosis, which was closely correlated with the total white cell count and with the activity of the disease. For patients with Crohn's disease, the peripheral blood monocyte count was also raised compared with that of the control groups, but the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 7 publications
3
25
1
Order By: Relevance
“…Leukocyte enhancement was due to the proportional increase in all type of leukocytes (data not shown), except for the group receiving the 2% dose of DSS, which showed a relatively higher amount of monocytes with respect to the control group at day 5 of treatment. This pattern of response has also been observed in patients with active episodes of IBD (30). Due to the severity of the hemorrhages developed by some of the DSS-treated rats, erythrocyte number and hematocrit were significantly diminished in animals in the 2% DSS group after 5 days, and at day 7 there was a further reduction (70% decrease) in both variables with respect to the values for control animals.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…Leukocyte enhancement was due to the proportional increase in all type of leukocytes (data not shown), except for the group receiving the 2% dose of DSS, which showed a relatively higher amount of monocytes with respect to the control group at day 5 of treatment. This pattern of response has also been observed in patients with active episodes of IBD (30). Due to the severity of the hemorrhages developed by some of the DSS-treated rats, erythrocyte number and hematocrit were significantly diminished in animals in the 2% DSS group after 5 days, and at day 7 there was a further reduction (70% decrease) in both variables with respect to the values for control animals.…”
Section: Resultssupporting
confidence: 50%
“…In the present study, the activation of the immune response is consistent with the observed dose-response increase in circulating leukocytes (r = 0.77, P = 0.000001). Furthermore, the increase in the percentage of circulating monocytes at the 2% DSS dose might be explained by the active recruitment of monocytes into the inflamed tissue, as has been described in patients with active IBD (30).…”
Section: Discussionmentioning
confidence: 95%
“…Fecal calprotectin is our best clinically available biomarker of disease activity in UC patients, but is limited in routine practice by cost, sample processing time, and ability to collect stool samples 25 . The use of peripheral blood leukocyte subtypes as biomarkers of inflammatory disorders, including IBD, have been recently described 10,11,12,13,14,17,18,26. Complete blood counts with differential are almost universally monitored at clinic visit and thus routinely available.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils and peripheral blood mononuclear cells (PMBCs) were found to correlate with disease activity and predict disease severity in rheumatoid arthritis (RA) and acute coronary syndrome. 10, 11, 12 Alterations of leukocyte numbers, in particular monocytes, were recognized early on in IBD 13,14,15 . Indeed monocytes, macrophages and neutrophils are uniquely involved in the pathophysiology of IBD.…”
Section: Introductionmentioning
confidence: 99%
“…When the balance of the immune system is disturbed, through genetic or environmental challenges, the activated blood cells enter the intestinal submucosa and induce inflammation, which in turn attracts additional immune cells in a vicious circle. Patients with active IBD display increased numbers of circulating granulocytes and monocytes [10,11], which are assumed to be en route to the inflamed bowel mucosa. Subsequent differentiation of the CD14 + monocytes into TNF-α-producing (M1) macrophages in the mucosa fuels the inflammation and contributes to epithelial disruption and inflammation [12].…”
Section: Introductionmentioning
confidence: 99%